Prospective Study of Dobutamine Stress Echocardiography in Comparison with 18F-fluorodeoxyglucose Positron Emission Tomography for Myocardial Viability in Ischemic Cardiomyopathy - Nuthalapati Rama Kumari; Arumulla Sunitha; Sama Rajashekhar (Journal of Indian College of Cardiology)
Background: Myocardial viability is utilized in the decision-making process for suitability of revascularization in patients with coronary artery disease and depressed left ventricular (LV) function. Aims: The aim of this study was to compare the accuracy of dobutamine stress echocardiography (DSE) with the 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) for the identification of viable myocardium in patients with previous myocardial infarction and LV dysfunction. Settings and Design: This was a prospective observational study done at Nizam’s Institute of Medical Sciences. Materials and Methods: Patients with coronary artery disease with previous myocardial infarction with significant LV dysfunction were included in the study. Statistical Analysis: Categorical variables were presented in number and percentage (%), and continuous variables were presented as mean ± standard deviation. Student’s paired t-test was applied to test the difference between the outcomes of 18F-FDG PET and dobutamine stress echo. The statistical software SPSS 17.0 version was used in the analysis of the data. Results: In our study population, the mean LV ejection fraction was 35.1%. A total of 800 myocardial segments were evaluated with resting two-dimensional echocardiography examination, of which 250 (31.2%) were normal and 550 (68.8%) were abnormal segments. The dysfunctional 550 segments were further assessed with DSE followed by 18F-FDG PET. In our study, 453 segments were viable on 18F-FDG PET and 407 segments viable on DSE (P = 0.001). Viability was detected by both modalities in 88.1% and discordance in 11.9% of segments. These results yielded a positive predictive value of 97.8% and negative predictive value of 61.1% of DSE. Conclusions: On considering 18F-FDG PET a gold standard for detection of viable myocardial segments, DSE has shown a sensitivity of 87.6% and specificity of 90.7%. Thus, DSE can be used as a good alternate to 18F-FDG PET where facility for FDG PET is not available. However, patients detected to have nonviable dysfunctional segments on DSE can be evaluated further with 18F-FDG PET for confirmation of viability.